2015
DOI: 10.1128/jvi.03137-14
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Highly Pathogenic Avian Influenza A(H5N1) Virus PB1-F2 Variants and Their Virulence in BALB/c Mice

Abstract: Influenza A viruses (IAVs) express the PB1-F2 protein from an alternate reading frame within the PB1 gene segment. The roles of PB1-F2 are not well understood but appear to involve modulation of host cell responses. As shown in previous studies, we find that PB1-F2 proteins of mammalian IAVs frequently have premature stop codons that are expected to cause truncations of the protein, whereas avian IAVs usually express a full-length 90-amino-acid PB1-F2. However, in contrast to other avian IAVs, recent isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…This sample also contained the PB1-F2 S66 marker, which has been associated with increased pathogenicity in mammals (Conenello et al, 2011). In chickens, PB1-F2 has been implicated in increasing the duration of virus shedding upon infection and lowering pathogenicity (Kamal et al, 2015;Krumbholz et al, 2011;Zell et al, 2007). We also found N and T at position 66; interestingly, PB1-F2 T66 was only found in samples (n = 3 samples) sequenced through swab-NGS.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This sample also contained the PB1-F2 S66 marker, which has been associated with increased pathogenicity in mammals (Conenello et al, 2011). In chickens, PB1-F2 has been implicated in increasing the duration of virus shedding upon infection and lowering pathogenicity (Kamal et al, 2015;Krumbholz et al, 2011;Zell et al, 2007). We also found N and T at position 66; interestingly, PB1-F2 T66 was only found in samples (n = 3 samples) sequenced through swab-NGS.…”
Section: Discussionmentioning
confidence: 68%
“…The presence of PB1-F2 T66 in databases is low, suggesting either low circulation of this marker in avian species and/or detection bias. In chickens, PB1-F2 has been implicated in increasing the duration of virus shedding upon infection and lowering pathogenicity (Kamal et al, 2015;Krumbholz et al, 2011;Zell et al, 2007). The consequence of the total length and residue preference at position 66 in PB1-F2 for fitness in natural hosts remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been reported that approximately 61 % of HPAI H5N1 isolates from 2013 had a truncated PB1-F2 (Kamal et al , 2015); therefore we also examined if avian virus pathogenicity as defined by a multiple basic cleavage site (two or more basic aa), in the HA protein, was associated with PB1-F2 length. We found little variation in the frequency of full-length PB1-F2 in HPAI or LPAI viruses and a marginal reduction in HPAI (87.7 % HPAI vs 91.0 % LPAI) was entirely due to the H5 subtype (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…More than half of all human and swine isolate sequences deposited in the public sequence databases encode a PB1-F2 less than 90 aa in length. In contrast, more than 90 % of sequences from isolates sequenced from avian hosts retain the coding capacity for a full-length PB1-F2 protein (Kamal et al , 2015; Zell et al , 2007). This disparity of PB1-F2 full-length conservation between virus isolates from mammalian and avian hosts suggests a unique pressure to maintain a full-length PB1-F2 protein with evolutionary significance in avian hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the alternative reading frame of the polymerase basic protein 1 of the WA2 viruses is truncated (57 aa long), as it is in the Asian and European progenitors. This truncation is common among influenza A viruses of mammals and in HPAI A(H5N1) viruses, and it has been associated with increased virulence in mammals ( 12 ). …”
Section: The Studymentioning
confidence: 99%